PROGNOSIS OF THE ACUTE PHASE COURSE OF TRAUMATIC DISEASE AND TRANSPORTABILITY IN POLYTRAUMA PATIENTS - O. N. Ergashev; A. I. Makhnovskiy; S. I. Krivonosov (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The aim of the study was to substantiate the criteria for predicting of the acute phase course of traumatic disease and transportability in polytrauma patients. MATERIAL AND METHODS. The course of traumatic disease was studied in 233 patients. The prognostic value of the ISS, RTS, TRISS scores and Russian VPH-P, VPH-SP and Tsybin scores was studied using the method of binary logistic regression, Roc analysis and correlation analysis. RESULTS. RTS (AUC=0.93), TRISS (AUC=0.86) and Russian VPH-P (AUC=0.74) scores have the highest prognostic value. There is a strong correlation between the RTS and TRISS scores (r =+0.90). CONCLUSION. It is advisable to use the RTS score and Russian VPH-P score to predict the acute phase course of traumatic disease and transportability in polytrauma patients.